A composite bipolar plate for flow batteries and a method of making the same
Patent Information
- Application Number
- CN202311189027.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-09-15
AI Technical Summary
传统双极板通常使用石墨或碳塑复合材料通过模压或挤出等方法加工成型,石墨双极板虽然导电性能好,但加工难度大,机械性能差,成本高,而碳塑复合材料双极板虽然机械强度好、成本低、易加工,但是导电性能不如石墨双极板,与电极的接触电阻也大
[0013]1、采用双金属中心原子结构的钛铝复合偶联剂,而不是简单的将酞酸酯和铝酸脂混合,相对于传统偶联剂具有更加优异的偶联效果,大大提高导电碳材料无机物与聚合物的相容性。
Smart Images

Figure CN117133937B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flow battery technology, specifically relating to a composite bipolar plate for flow batteries and its preparation method. Background Technology
[0002] Flow batteries are a new type of environmentally friendly chemical energy storage battery with advantages such as high energy conversion efficiency, convenient site selection, safe operation, and long service life, and have broad application prospects. As the main component of a flow battery, the bipolar plate primarily connects and supports the positive and negative electrodes of the battery cells in the stack, collects electrons, and isolates the positive and negative electrolytes. Therefore, the bipolar plate needs to have good conductivity, low contact resistance, resistance to electrolyte corrosion, and good barrier properties. Traditional bipolar plates are usually made of graphite or carbon-plastic composite materials through molding or extrusion. While graphite bipolar plates have good conductivity, they are difficult to process, have poor mechanical properties, and are expensive. Carbon-plastic composite bipolar plates, while having good mechanical strength, low cost, and easy processing, have lower conductivity than graphite bipolar plates and higher contact resistance with the electrodes. Existing technologies attempt to form a conductive network by incorporating metal mesh or carbon fiber cloth within the bipolar plate, or by applying a conductive layer to the surface of the bipolar plate to reduce contact resistance, and corresponding preparation methods have been disclosed. However, none of these methods can achieve continuous production, nor can they guarantee sufficient bonding between the network material or coating and the bipolar plate substrate. Furthermore, the coating only serves to reduce contact resistance, exhibiting a limited function. The technical solutions disclosed in CN201811026544.X and CN201110459942.2 involve hot-pressing carbon felt and bipolar plate material together to reduce contact resistance. However, the hot-pressing process severely damages the pore structure and alters the porosity of the carbon felt, significantly affecting the uniform and sufficient flow of the electrolyte between the pores of the carbon felt electrode. Summary of the Invention
[0003] To address the aforementioned problems, this invention provides a composite bipolar plate for flow batteries and its preparation method. The bipolar plate prepared by this method exhibits high mechanical strength, good conductivity, and low contact resistance, improving electrolyte reaction efficiency, reducing side reactions, and significantly minimizing the thermal shrinkage rate of the bipolar plate. It can be applied to various scenarios such as thermoforming welding, laser welding, and mechanical sealing. Furthermore, the preparation method provided by this invention enables continuous production, resulting in high production efficiency, stable product quality, and low production costs.
[0004] The technical solution of this invention is:
[0005] A composite bipolar plate for a flow battery includes a thermoplastic conductive plastic layer, a carbon material surface felt, a negative electrode carbon material coating, and a positive electrode carbon material coating. The thermoplastic conductive plastic layer is composed of 32% to 63% thermoplastic resin, 35% to 65% conductive carbon material powder, 0.5% to 2% rare earth aluminum-titanium composite coupling agent, 0.1% to 0.5% antioxidant, and 0.3% to 1.5% lubricant by weight. The carbon material surface felt is located on both sides of the thermoplastic conductive plastic layer, and the thickness of the carbon material surface felt is 0.05mm~0.15mm. The negative electrode carbon material coating and the positive electrode carbon material coating are respectively located on both sides of the carbon material surface felt. The negative electrode carbon material coating is composed of 92%~95.5% conductive carbon black powder, 1%~3% low molecular weight polyisobutylene, 3%~5% EEA resin powder, and 0.5%~1.5% tin chloride powder by weight. The positive electrode carbon material coating is composed of 11%~35% conductive carbon black powder, 60%~80% flake graphite powder, 1%~3% low molecular weight polyisobutylene, 3%~5% EEA resin powder, 0.5%~1.5% tin chloride powder, and 0.3%~1% titanium dioxide powder by weight. The number average molecular weight of the low molecular weight polyisobutylene is 1000~2000; The weight percentage of EA in the EEA resin is 20% to 30%.
[0006] Furthermore, in the aforementioned composite bipolar plate for a flow battery, the thermoplastic resin is one or more of polyethylene, polypropylene, poly-1-butene, poly-1-pentene, PVDF, POE, TPV, and EPDM, preferably a composition of 80% to 95% by weight of high-density polyethylene or polypropylene and 5% to 20% by weight of POE or TPV.
[0007] Furthermore, in the aforementioned composite bipolar plate for a flow battery, the conductive carbon material powder is one or more of carbon black, flake graphite, and carbon fiber powder.
[0008] Furthermore, in the aforementioned composite bipolar plate for a flow battery, the carbon material surface felt is graphitized PAN surface felt or carbon fiber surface felt.
[0009] Furthermore, in the aforementioned composite bipolar plate for a flow battery, the thickness of both the negative electrode carbon material coating and the positive electrode carbon material coating is 0.02 mm to 0.06 mm.
[0010] The above-mentioned method for preparing a composite bipolar plate for a flow battery includes the following steps: Step 1: Weigh the thermoplastic resin, conductive carbon powder, rare earth aluminum-titanium composite coupling agent, antioxidant, and lubricant according to the specified proportions and add them to a mixing mill for mixing. The first stage mixing temperature is 80℃~135℃, the first stage rotor speed is 60r / min~80r / min, and the first stage mixing time is 5min~10min; the second stage mixing temperature is 170℃~235℃, the second stage rotor speed is 30r / min~50r / min, and the second stage mixing time is 5min~15min; after the mixed material is cooled, it is crushed using a crusher with a screen aperture of 8mm~10mm to obtain crushed material. Step 2: Add conductive carbon black powder, low molecular weight polyisobutylene, EEA resin powder, and tin chloride powder to a high-speed mixer in proportion to obtain the negative electrode carbon material coating mixture. The mixer speed is 1200 r / min~1800 r / min. Add conductive carbon black powder, flake graphite powder, low molecular weight polyisobutylene, EEA resin powder, tin chloride powder, and titanium dioxide powder to a high-speed mixer in proportion to obtain the positive electrode carbon material coating mixture. The mixer speed is 1200 r / min~1800 r / min. Step 3: Add the crushed material obtained in Step 1 into a twin-screw extruder, and extrude it into a sheet blank through a sheet extrusion die connected to the extruder. The length-to-diameter ratio of the twin-screw extruder screw is 48:1~40:1, the barrel temperature is 160℃~235℃, the die temperature is 235℃~260℃, and the screw speed is 40r / min~90r / min. Step 4: Apply the carbon material surface felt to both sides of the sheet blank extruded in Step 3. Then, place a 0.05mm~0.08mm thick PET or PTFE film on the outside of the carbon material surface felt. Then, use a pair of hot rollers to press the carbon material surface felt and the sheet blank together. The roller temperature is 150℃~190℃, and the gap between the hot rollers is 80%~90% of the sheet blank thickness. After the sheet passes through the gap between the hot rollers, peel off the PET or PTFE film. Step 5: Add the positive and negative carbon material coating mixtures prepared in Step 2 to the positive and negative slit powder coating machines respectively. Apply powder coating to the composite sheet after Step 4 through the nozzle. The slit is 0.1mm~1mm and the spraying air pressure is 0.05MPa~0.2MPa. Then, use a pair of cold rollers to compact the coated sheet coating. The temperature of the cold rollers is 50℃~70℃. Step 6: After spraying and cold pressing, the sheet material passes through the shaping roller, tension roller, traction roller, and cutting machine in sequence to obtain the bipolar plate.
[0011] Furthermore, in the above-mentioned method for preparing a composite bipolar plate for a flow battery, the hot roller and the cold roller rotate at the same speed, and the traction roller is torque-controlled with a torque of 9 Nm to 11 Nm.
[0012] Advantages and beneficial effects of the present invention:
[0013] 1. A titanium-aluminum composite coupling agent with a bimetallic central atomic structure is used instead of a simple mixture of phthalate and aluminate. Compared with traditional coupling agents, it has a better coupling effect and greatly improves the compatibility between inorganic materials and polymers in conductive carbon materials.
[0014] 2. Using polyisobutylene of appropriate molecular weight and EEA of appropriate EA content as binders, it has the characteristics of low melting point, good adhesion to polymers and inorganic materials such as carbon fillers, and good chemical stability compared with existing PVDF and other resins.
[0015] 3. The composition of the carbon material coatings for the positive and negative electrodes of the bipolar plate is designed separately according to the different side reaction mechanisms of the positive and negative electrodes of the battery. Different materials and formulations are used to increase the hydrogen evolution overpotential of the negative electrode and the oxygen evolution overpotential of the positive electrode, and reduce the occurrence of hydrogen evolution and oxygen evolution side reactions of the negative electrode and the positive electrode. At the same time, the graphite and titanium dioxide in the positive electrode carbon material can also reduce the occurrence of positive electrode carbon oxidation side reaction. However, the existing technology does not distinguish between positive and negative electrode materials and does not have the function of reducing the occurrence of battery side reactions.
[0016] 4. The mixing process of thermoplastic conductive plastics is divided into two stages. The first stage is carried out at a low temperature and high speed, which is conducive to the thorough mixing and wetting of additives and conductive fillers. The second stage is carried out at a high temperature and slow speed to avoid resin degradation due to excessive shearing, and at the same time to avoid damage to the mixer due to excessive torque.
[0017] 5. Using PET or PTFE film as a pad, hot pressing is performed on the molten bipolar plate sheet blank and the carbon material surface felt. After hot pressing, the PET or PTFE film is peeled off, which avoids the molten blank sticking to the hot roller, ensures the flatness of the sheet blank surface, and ensures the spraying of coating materials.
[0018] 6. The hot roller extrusion method is used to laminate the molten blank and the carbon material surface felt. This ensures that the molten conductive plastic material is fully filled into the surface felt, so that the surface felt is completely impregnated into the conductive plastic sheet blank. At the same time, it can be produced continuously. Compared with the molding process, it has the advantages of high production efficiency, low manufacturing cost and flexible product specifications and dimensions.
[0019] 7. The slit and width of the slit spray nozzle can be adjusted, allowing for continuous or intermittent spraying with adjustable spray intervals. This enables the formation of coatings of different sizes on the surface of the bipolar plate to meet the requirements of electrodes of different sizes. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the composite bipolar plate structure for the flow battery of the present invention; Figure 2 This is a cross-sectional view of the composite bipolar plate for the flow battery of the present invention; Figure 3 A schematic diagram of the apparatus for preparing the flow battery of the present invention; Figure 4 This is a schematic diagram of the coating nozzle area; In the diagram, 1-thermoplastic conductive plastic layer, 2-carbon material surface felt, 3-negative electrode carbon material coating, 4-positive electrode carbon material coating, 101-twin-screw extruder, 102-sheet extrusion die, 103-tensioning roller, 104-carbon material surface felt feeding roller, 105-PET film / PTFE film feeding roller, 106-hot press roller, 107-PET film / PTFE film receiving roller, 108-negative electrode coating nozzle, 109-positive electrode coating nozzle, 110-powder recovery hood, 111-cold press roller, 112-shaping roller, 113-traction roller, 114-cutting machine. Detailed Implementation
[0021] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. The following examples are for illustrative purposes only and should not be used to limit the scope of the present invention.
[0022] like Figures 1-2 As shown, a composite bipolar plate for a flow battery includes a thermoplastic conductive plastic layer 1, a carbon material surface felt 2, a negative electrode carbon material coating 3, and a positive electrode carbon material coating 4. The carbon material surface felt 2 is located on both sides of the thermoplastic conductive plastic layer 1, and the negative electrode carbon material coating 3 and the positive electrode carbon material coating 4 are located on both sides of the carbon material surface felt 2.
[0023] Example 1
[0024] The component ratios and preparation methods of the bipolar plate in this embodiment are as follows: Weigh out 37.8% high-density polyethylene, 4.2% POE, 45% conductive carbon black, 10% carbon fiber powder, 1.5% rare earth aluminum-titanium composite coupling agent, 0.3% antioxidant, and 1.2% lubricant by weight, and add them to an internal mixer for mixing. The first mixing temperature is 95℃, the rotor speed is 70 r / min, and the mixing time is 8 min. The second mixing temperature is 195℃, the rotor speed is 40 r / min, and the mixing time is 10 min. After cooling, the mixed material is crushed using a crusher with a screen aperture of 10 mm to obtain crushed material. like Figures 1-4As shown, the above-mentioned crushed material is added to the twin-screw extruder 101 and extruded into a sheet blank through the sheet extrusion die 102 connected to the twin-screw extruder 101. The length-to-diameter ratio of the screw of the twin-screw extruder 101 is 44:1, the barrel temperature is 160℃~235℃, the die temperature is 235℃~260℃, and the screw speed is 60 r / min. A 0.05mm thick graphitized PAN surface felt is installed onto the carbon material surface felt feeding roller 104, and a 0.06mm thick PET film is installed onto the PET film / PTFE film feeding roller 105. The graphitized PAN surface felt and PET film are fed together and, after passing through the tension roller 103, are respectively attached to both sides of the sheet blank extruded in step 3. Then, a pair of hot press rollers 106 are used to press the PET film, surface felt, and resin sheet blank. The roller temperature is 160℃, and the gap between the hot press rollers 106 is 85% of the thickness of the resin sheet blank. After the sheet passes through the gap of the hot press rollers 106, the PET film is torn off and removed, and then wound onto the PET film / PTFE film receiving roller 107 for recycling. Weigh out 94% conductive carbon black powder, 2.0% oligoisobutylene with a molecular weight of 2000, 4.0% EEA resin powder with an EA content of 23%, and 1.0% tin chloride powder as the negative electrode carbon material coating 3. Weigh out 25% conductive carbon black powder, 66% flake graphite powder, 3.0% oligoisobutylene with a molecular weight of 2000, 4.5% EEA resin powder with an EA content of 23%, 1.0% tin chloride powder, and 0.5% titanium dioxide powder as the positive electrode carbon material coating 4. Add the weighed negative electrode carbon material coating 3 and positive electrode carbon material coating 4 into a high-speed mixer and mix them at a speed of 1400 r / min. The mixed positive electrode carbon material coating 4 and negative electrode carbon material coating 3 are added to the positive and negative electrode slit powder coating machines, respectively. The sheet after the composite in step 4 is powder coated by the negative electrode coating nozzle 108 and the positive electrode coating nozzle 109. The nozzle slit is 0.5mm and the spraying air pressure is 0.1MPa. The powder that does not adhere to the sheet surface and splashes out is recycled by the powder recovery hood 110. Then, a pair of cold pressure rollers 111 are used to compact the coated sheet coating. The temperature of the cold rollers is 65℃. After being sprayed and cold-pressed, the sheet passes through the shaping roller 112 at a temperature of 65°C, and then through the tensioning roller 103, traction roller 113, and cutting machine 114 to obtain the bipolar plate.
[0025] The hot pressing roller 106, cold pressing roller 111 and shaping roller 112 all rotate at 1.2 m / min, and the traction roller 113 is torque controlled with a torque of 10 Nm.
[0026] The above detailed description of the present invention is for illustrative purposes only and is not intended to limit the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that modifications or equivalent substitutions can still be made to the present invention to achieve the same technical effect; as long as the usage needs are met, they are all within the protection scope of the present invention.
Claims
1. A composite bipolar plate for a flow battery, comprising a thermoplastic conductive plastic layer (1), a carbon material surface felt (2), a negative electrode carbon material coating (3), and a positive electrode carbon material coating (4), characterized in that, The thermoplastic conductive plastic layer (1) is composed of 32%~63% thermoplastic resin, 35%~65% conductive carbon material powder, 0.5%~2% rare earth aluminum titanium composite coupling agent, 0.1%~0.5% antioxidant, and 0.3%~1.5% lubricant by mass. The carbon material surface felt (2) is located on both sides of the thermoplastic conductive plastic layer (1), and the thickness of the carbon material surface felt (2) is 0.05mm~0.15mm. The negative electrode carbon material coating (3) and the positive electrode carbon material coating (4) are located on both sides of the carbon material surface felt (2). The negative electrode carbon material coating (3) is composed of 92%~95.5% conductive carbon black powder, 1%~3% low molecular weight polyisobutylene, 3%~5% EEA resin powder, and 0.5%~1.5% tin chloride powder by mass. The positive electrode carbon material coating (4) is composed of 11%~35% conductive carbon black powder, 60%~80% flake graphite powder, 1%~3% low molecular weight polyisobutylene, 3%~5% EEA resin powder, 0.5%~1.5% tin chloride powder, and 0.3%~1% titanium dioxide powder by mass. The thickness of both the negative electrode carbon material coating (3) and the positive electrode carbon material coating (4) is 0.02 mm to 0.06 mm; The number average molecular weight of the low molecular weight polyisobutylene is 1000~2000; The weight percentage of EA in the EEA resin is 20% to 30%.
2. The composite bipolar plate for a flow battery according to claim 1, characterized in that, The thermoplastic resin is one or more of polyethylene, polypropylene, poly-1-butene, poly-1-pentene, PVDF, POE, TPV, and EPDM.
3. A composite bipolar plate for a flow battery according to claim 1, characterized in that, The conductive carbon material powder is one or more of conductive carbon black, flake graphite, and carbon fiber powder.
4. A composite bipolar plate for a flow battery according to claim 1, characterized in that, The carbon material surface felt (2) is a graphitized PAN surface felt or a carbon fiber surface felt.
5. A method for preparing a composite bipolar plate for a flow battery according to any one of claims 1 to 4, characterized in that, Includes the following steps: Step 1: Weigh the thermoplastic resin, conductive carbon powder, rare earth aluminum-titanium composite coupling agent, antioxidant, and lubricant according to the specified proportions and add them to a mixing mill for mixing. The first stage mixing temperature is 80℃~135℃, the first stage rotor speed is 60r / min~80r / min, and the first stage mixing time is 5min~10min; the second stage mixing temperature is 170℃~235℃, the second stage rotor speed is 30r / min~50r / min, and the second stage mixing time is 5min~15min; after the mixed material is cooled, it is crushed using a crusher with a screen aperture of 8mm~10mm to obtain crushed material. Step 2: Add conductive carbon black powder, low molecular weight polyisobutylene, EEA resin powder, and tin chloride powder to a high-speed mixer in proportion to obtain the negative electrode carbon material coating mixture. The mixer speed is 1200 r / min~1800 r / min. Add conductive carbon black powder, flake graphite powder, low molecular weight polyisobutylene, EEA resin powder, tin chloride powder, and titanium dioxide powder to a high-speed mixer in proportion to obtain the positive electrode carbon material coating mixture. The mixer speed is 1200 r / min~1800 r / min. Step 3: Add the crushed material obtained in Step 1 into a twin-screw extruder, and extrude it into a sheet blank through a sheet extrusion die connected to the extruder. The length-to-diameter ratio of the screw in the twin-screw extruder is 48:1~40:1, the barrel temperature is 160℃~235℃, the die temperature is 235℃~260℃, and the screw speed is 40r / min~90r / min. Step 4: Apply the carbon material surface felt (2) to both sides of the sheet blank extruded in Step 3. Then, place a 0.05mm~0.08mm thick PET film or PTFE film on the outside of the carbon material surface felt (2). Then, use a pair of hot rollers to press the carbon material surface felt (2) and the sheet blank together. The roller temperature is 150℃~190℃ and the gap between the hot rollers is 80%~90% of the thickness of the sheet blank. After the sheet passes through the gap between the hot rollers, tear off the PET film or PTFE film. Step 5: Add the positive and negative carbon material coating mixtures prepared in Step 2 to the positive and negative slit powder coating machines respectively. Apply powder coating to the composite sheet after Step 4 through the nozzle. The slit is 0.1mm~1mm and the spraying air pressure is 0.05MPa~0.2MPa. Then, use a pair of cold rollers to compact the coated sheet coating. The temperature of the cold rollers is 50℃~70℃. Step 6: After spraying and cold pressing, the sheet material passes through the shaping roller, tension roller, traction roller and cutting machine in sequence to obtain the bipolar plate.
6. The method for preparing a composite bipolar plate for a flow battery according to claim 5, characterized in that, The hot and cold rollers rotate at the same speed, and the traction roller is torque-controlled with a torque of 9 Nm to 11 Nm.
Citation Information
Patent Citations
Bipolar plate of integrated composite electrode, and manufacturing method and application thereof
CN102569824A
Integrated electrode-bipolar plate structure and fabrication method
CN110875483B
Preparation method of graphite felt modified electrode and all vanadium flow battery
CN102544526A
Weldable bipolar plate for flow battery and preparation and application thereof
CN111261891A